Kedudukan Istri dalam Pembagian Harta Bersama Akibat Putusnya Perkawinan Karena Perceraian Terkait Kerahasiaan Bank - Wijayanti, Winda (Mahkamah Konstitusi Republik Indonesia, 2013)
Marriage is something sacred, must be respected, the eternality of which must be protected and conducted jointly between a man and a woman as husband and wife so as to achieve a common goal. However, in reality, lots of marriages end with divorce and is considered as the best way for both partners. When a divorce occurs women is always in a weak position including in the divison of marital property if one party does not have a good faith. Bank as the depository institution maintains the confidentiality of depositors and their deposit which is on the one hand beneficial for depositors since information related to depositors and their deposit can be kept confidential, but on the other hand, it is disadvantageous to interested parties that is a wife who does not know the amount of funds deposited in her husband’s name in a bank which is a marital property of husband and wife acquired during their marriage. Thus, the wife’s constitutional rights to protection of property under his control and property rights in accordance with Article 28G paragraph (1) and Article 28H Paragraph (4) of the 1945 Constitution is not protected. The Constitutional Court as the guardian of the constitution has the authority to examine, try and decide the case of judicial review of Law No. 1 of 1974 on Marriage (Marriage Act) and declare the law conditionally constitutional in the case of bank confidentiality regarding information related to depositors and their deposit to the interests of justice in a civil case concerning the division of maritall property due to divorce.